Cholesterol depletion impairs contractile machinery in neonatal rat cardiomyocytes - Hissa, Barbara (Sci Rep, 2017)
Cholesterol regulates numerous cellular processes. Depleting its synthesis in skeletal myofibers induces vacuolization and contraction impairment. However, little is known about how cholesterol reduction affects cardiomyocyte behavior. Here, we deplete cholesterol by incubating neonatal cardiomyocytes with methyl-beta-cyclodextrin. Traction force microscopy shows that lowering cholesterol increases the rate of cell contraction and generates defects in cell relaxation. Cholesterol depletion also increases membrane tension, Ca(2+) spikes frequency and intracellular Ca(2+) concentration. These changes can be correlated with modifications in caveolin-3 and L-Type Ca(2+) channel distributions across the sarcolemma. Channel regulation is also compromised since cAMP-dependent PKA activity is enhanced, increasing the probability of L-Type Ca(2+) channel opening events. Immunofluorescence reveals that cholesterol depletion abrogates sarcomeric organization, changing spacing and alignment of α-actinin bands due to increase in proteolytic activity of calpain. We propose a mechanism in which cholesterol depletion triggers a signaling cascade, culminating with contraction impairment and myofibril disruption in cardiomyocytes.